Investigation of a New Catheter on Relieving Pain During Male Cystoscopy–a Randomized Clinical Trial - Jiang, Xiong Yong; Jiaji, Liu; Tao, Zhao (Urology Journal, 2020)
Purpose: To investigate the pain intensity and tolerability of a new catheter applied to urethral surface anesthesia during rigid cystoscopy in male patients, and explore the prospects of its application and the anesthetic method in hospitals at primary levels. Materials and Methods: 252 adult male patients were randomly divided into the experimental group and the control group.1% lidocaine solution was irrigated into the posterior urethra of the experimental group using the new catheter before cystoscopy, while the control group was administered with lidocaine gel. Both groups were assessed by visual analogue scale(VAS) with their pain perceived during administration of lidocaine (control group) /during insertion of catheter and administration of lidocaine (experimental group) (T1),during the insertion of cystoscope (T2),at the beginning of cystoscopy (T3),The third minute of cystoscopy (T4), during the first urination after the procedure (T5), as well with the maximum pain(Pmax) perceived during the whole procedure. The fluctuations of blood pressure and heart rate in each group before, after and during the procedure were recorded, and the anesthesia costs in both groups were calculated. Results: Except a slightly higher score in T1, the scores of VAS in experimental group were lower than those of control group in T2,T3 and T4. The Pmax of the control group was 4.92(SD=1.20), which was higher than in the experimental group of 3.89(SD=0.95,P<0.01).There was no significant difference on blood pressure variation in both groups. While heart rate variation in experimental group was lower than that in control group (16.3%,SD=3.4 vs. 22.6%,SD=5.0, P<0.01).No obvious complications were found in both groups. The anesthesia cost of the experimental group is about 1.53 dollars, with 1.75 dollars lower than that of the control group. Conclusion: It is tolerable and beneficial to apply the new catheter for male urethral anesthesia. It can significantly relieve the pain during rigid cystoscopy in male patients, and is low in cost and easy in operation. Thus this method is worth being recommended to hospitals, especially at community hospitals or primary hospitals.